Answer:
(2 (4 x + 5), -(3 x + 25))
Explanation:
Simplify the following:
(12 x - 4 x + 3 + 7, 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8)
Grouping like terms, 12 x - 4 x + 3 + 7 = (12 x - 4 x) + (3 + 7):
((12 x - 4 x) + (3 + 7), 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8)
12 x - 4 x = 8 x:
(8 x + (3 + 7), 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8)
3 + 7 = 10:
(8 x + 10, 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8)
Factor 2 out of 8 x + 10:
(2 (4 x + 5), 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8)
Grouping like terms, 5 x + 2 x - 3 x - 7 x - 18 - 13 - 2 + 8 = (-7 x + 2 x - 3 x + 5 x) + (8 - 13 - 18 - 2):
(2 (4 x + 5), (-7 x + 2 x - 3 x + 5 x) + (8 - 13 - 18 - 2))
-7 x + 2 x - 3 x + 5 x = -3 x:
(2 (4 x + 5), -3 x + (8 - 13 - 18 - 2))
8 - 13 - 18 - 2 = -25:
(2 (4 x + 5), -25 - 3 x)
Factor -1 out of -3 x - 25:
Answer: (2 (4 x + 5), -(3 x + 25))